Production, characterization and therapeutic efficacy of egg yolk antibodies specific to Nosema ceranae - Acik, Mehmet Nuri; Karagulle, Burcu; Yakut, Seda; Ozturk, Yasin; Kutlu, Mehmet Ali; Kalin, Recep; Cetinkaya, Burhan (Public Library Science, 2024)
Nosema disease, caused by Nosema ceranae, one of the single-celled fungal microsporidian parasites, is one of the most important and common diseases of adult honey bees. Since fumagillin, which has been used for decades in the control of Nosema disease in honey bees (Apis mellifera), poses a toxic threat and its efficacy against N. ceranae is uncertain, there is an urgent need to develop alternative prophylactic and curative strategies for the treatment of this disease. The main aim of this study was to investigate the therapeutic potential of specific egg yolk immunoglobulins (IgY) on Nosema disease. For this purpose, the presence of N. ceranae was determined by microscopic and PCR methods in honey bees collected from Nosema suspicious colonies by conducting a field survey. Layered Ataks chickens, divided into four groups each containing 20 animals, were vaccinated with live and inactivated vaccines prepared from field isolates of N. ceranae. Eggs were collected weekly for 10 weeks following the last vaccination. IgY extraction was performed using the PEG precipitation method from egg yolks collected from each group, and the purity of the antibodies was determined by SDS-PAGE and Western Blot. The presence of N. ceranae-specific IgYs was investigated by Western Blot and indirect ELISA methods. It was determined that specific IgYs showed high therapeutic efficacy on Nosema disease in naturally infected bee colonies. In addition, honey bees collected from infected colonies were brought to the laboratory and placed in cages with 30 bees each, and the effectiveness of IgYs was investigated under controlled conditions. It was detected that specific IgY reduced the Nosema spore load and the number of infected bees significantly in both the field and experimental study groups treated for seven days. It was concluded that chicken IgYs, an innovative and eco-friendly method, had a significant potential for use as an alternative to antifungal drugs.
Keywords: Apis-Mellifera; Immunoglobulin-Y; Igy; Honey; Fumagillin; Infection; Dicyclohexylamine; Immunization; Proteins; Virus